Bacterial uptake of antimicrobial peptides - Irvalı, Deniz. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
The discovery of beta lactam antibiotics has been a groundbreaking improvement in the treatment of bacterial diseases. However, most bacteria have gained resistance against beta lactam antibiotics which rendered them ine ective. Beta lactamase mediated resistance is the most frequently encountered defence mechanism. To overcome this problem, several beta lactamase inhibitors have been developed such as clavulanic acid, sulbactam and tazobactam. They are generally small molecules that pose high a nity towards beta lactamase enzyme, thus protect beta lactam from being hydrolyzed. Unfortunately, bacteria started to produce di erent beta lactamases which are not sensitive to conventional inhibitors that led to the emergence of designing effective beta lactamase inhibitors. These inhibitors must have high a nity as well as good cell penetration capability to inhibit beta lactamase in the periplasmic space. In this study, the e ect of adding ve hydrophobic residues to beta lactamase inhibitory proteins was examined. The chimeric peptides P2,P4,P5, which included a hydrophobic part and an inhibitory part, and the inhibitory peptide P3 were examined for their inhibition properties and for their cell penetration capabilities sing in vivo and in vitro techniques. P2 showed uncompetitive inhibition with Ki of 36 M and P3 indicated competitive inhibition with Ki of 412.44 M. P4 decreased Km and Vmax around 85%. The cell growth experiments showed that P4 was the most e ective peptide that inhibited cell growth in resistant cells after 250 M.
Keywords: Peptide antibiotics.